Influence of dental calculus on tooth abnormalities in cats and contributing factors - Arnolia, Putri; Siagian, Tetty Barunawati (ARSHI Veterinary Letters, 2025)
Dental plaque is a thin biofilm composed of bacteria that accumulate on tooth surfaces. If not adequately removed, plaque can mineralize into dental calculus, which is associated with various oral health issues. In cats, this condition may lead to dental abnormalities, such as malocclusion and tooth resorption; however, reports from Indonesia remain limited. This study investigated the relationship between dental calculus and dental disorders in 45 cats, as well as the contributing factors of this relationship. Clinical examinations were performed to assess calculus formation and to identify dental abnormalities. A structured questionnaire was administered to cat owners regarding their oral health awareness and management practices. Data were analyzed descriptively and using Fisher’s Exact Test to evaluate the association between calculus and dental abnormalities. Of the 45 cats examined, 28 (62.2%) had dental calculus, of which eight (28.6%) exhibited dental abnormalities. Owner surveys revealed that although 82% were aware of tartar, only 8.9% reported performing routine dental examinations on their pets. In conclusion, dental calculus significantly contributes to the development of dental abnormalities in cats, with feeding habits identified as a key influencing factor.